Human Resource Management Planning at PT. Batang Hari Benulu Primary - Soni Ade Pratama; Evi Lorita; Harius Eko Saputra; Marida Sari Ningsih (Penerbit Jurnal Indonesia, 2022)
The objective of this research is to describe the Human Resource Management Planning at PT. Batang Hari Bengkulu Pratama. This research is categorized as a qualitative descriptive data collection by means of interviews, observation and documentation. The selection of informants was done by purposive sampling of five people with theory. According to Schuler's opinion, (1987: 62-78) it can be concluded that there are four important stages in the HR planning process of (1) Gathering, Analizing, and Forecasting Supply and Demand Data. Collecting, Analyzing, Predicting Supply and Demand Data. Employees at the company are given special training, recruitment of new employees complete the requirements, placement of employees in accordance with their expertise and are professional but employees still get knowledge and technology. (2) Establishing Human Resource Objectives and Policies. Setting HR goals and policies. Not all employees get training and seminars, only a certain section on education, no help with student fees for formal education provided by the company. (3) Humand Resource Programming. There are incentives for employees who reach the target, pension funds and layoffs are given by the company in accordance with the work period of employees who are 55 years old, calculated as working years, while employees who are laid off are calculated as their years of service in the company. (4) Humand Resource Planning-Control and Evaluation. HR Planning and Evaluation Control. Supervision and evaluation of employee performance is carried out by the foreman to laboratory analysis of the company leadership, there is no specific space for counseling. There is a special forum formed by the company to select employees who excel to be promoted and occupy certain positions.